Evolution of Globus Pallidus Targeting for Parkinson's and Dystonia Deep Brain Stimulation: A 15-Year Experience - Holanda, Vanessa M.; Eisinger, Robert Stephen; Almeida, Leonardo; Tsuboi, Takashi; Wang, Huimin; Okun, Michael S.; Deeb, Wissam; Patterson, Addie; Wagle Shukla, Aparna; Lobo Lopes, Janine; Foote, Kelly Douglas (Frontiers in Neurology, 2021)
Objective: The aim of this study is to evaluate the evolution of GPi DBS targeting. Methods: This retrospective, single-center study included patients implanted with GPi DBS leads for dystonia or PD during the years 2004 to 2018 at the University of Florida Fixel Institute for Neurological Diseases. Each patient underwent a high-resolution targeting study on the day prior to the surgery, which was fused with a high resolution CT scan that was acquired on the day of the procedure. Intraoperative target location was selected using a digitized 3D Schaltenbrand-Bailey atlas. All patients underwent a high-resolution head CT scan without contrast approximately one month after lead implantation and accurate measurement of neuroanatomical lead position was acquired after fusion of pre-operative and post-operative image studies. Results: We analyzed 253 PD patients with 352 leads and 80 dystonia patients with 141 leads. During 15 years of follow-up, lead locations in the PD group migrated more laterally (𝛽=0.09, p<0.0001; Figure 1a), posteriorly (slope (𝛽)=0.04, p<0.05; Figure 1b), and dorsally (𝛽=0.07, p<0.001; Figure 1c), whereas leads in the dystonia group did not significantly change position aside from a trend in the dorsal direction (𝛽=0.06, p=0.053; Figures 1d-f). Conclusion: The evolving target likely results from multiple factors including improvements in targeting techniques and clinical feedback intraoperatively and post-operatively. Our demonstrates the potential importance of a systematic post-operative DBS lead measurement protocol to ensure quality control and to inform and optimize DBS programming